2014
DOI: 10.5935/1808-8694.20140008
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ectopic and supernumerary parathyroid glands in patients with secondary and tertiary hyperparathyroidism: surgical description and correlation with preoperative ultrasonography and Tc99m-Sestamibi scintigraphy✩✩Please cite this article as: Andrade JS, Mangussi-Gomes J, Rocha LA, Ohe MN, Rosano M, Neves MC, et al. Localization of ectopic and supernumerary parathyroid glands in patients with secondary and tertiary hyperparathyroidism: Surgical description and correlation with preoperative ult

Abstract: The presence of ectopic and supernumerary PT in patients with renal hyperparathyroidism is significant. Although preoperative imaging tests did not locate most of ectopic glands, MIBI may be important for identifying ectopic PT in the mediastinal and thymic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Still, we do not encountered higher levels of recurrence in comparison with authors who perform thymectomy routinely, as shown in a previous publication. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Still, we do not encountered higher levels of recurrence in comparison with authors who perform thymectomy routinely, as shown in a previous publication. 19 …”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Although ultrasound and radionuclide scanning technology have matured a lot over the last few years, the failure in locating the entire parathyroid tissue still remains. [ 31 ] Tissue traction often results in parathyroid ectopic. [ 32 ] Therefore, preoperative parathyroid localization is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, an ectopic parathyroid gland located in the anterior mediastinum was identified as the culprit of hypercalcemia and tertiary HPT in this case. However, the localization of the ectopic parathyroid glands vary diversely, and the most common sites are in the retroesophageal and thymic regions [7]. Notably, scintigraphy with 99mTc-Sestamibi should be performed in cases of recurrence and persistence of hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%